Microstructure, wear resistance and cell proliferation ability of in situ synthesized Ti–B coating produced by laser alloying. (April 2015) - Wu, Y.; Wang, A.H.; Zhang, Z.; Xia, H.B.; Wang, Y.N.
Abstract: Ti–B titanium compound coating with satisfactory wear resistance and good cell proliferation ability was in situ synthesized by a laser alloying technique on a Ti6Al4V substrate. Microstructural analysis indicated that defect-free coating and good interface between the coating and the substrate were obtained. Microstructure and phase structure analysis revealed that the produced coating mainly exhibited dot-like crystals and included α-Ti, TiB, AlTi, AlTi2 and AlTi3, respectively. Microhardness and wear resistance test indicated that the microhardness and the wear resistance were improved greatly by laser alloying treatment in comparison with the substrate. Evaluation of cell proliferation showed that the produced coating was suitable for cell proliferation. Highlights: Ti–B compound coating was produced by laser alloying on Ti6Al4V. Microstructure and phase structure of the fabricated coating were analyzed. The fabricated coating exhibits better wear resistance than the Ti6Al4V. Surface of the fabricated coating is suitable for cell proliferation.